The average productivity of upland rice is still relatively low. Therefore, it is necessary to improve agronomic characters related to grain yields, maturity, and their adaptation in dry land. The aims of this research were to evaluate agronomic traits, genetic parameters such as genetic and phenotype variance, heritability and G x E interaction of rice mutant lines derived from gamma irradiation treatment on upland rice. This research was conducted in Situbondo and Madiun, during rain season. T - Ishak, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
The average productivity of upland rice is still relatively low. Therefore, it is necessary to improve agronomic characters related to grain yields, maturity, and their adaptation in dry land. The aims of this research were to evaluate agronomic traits, genetic parameters such as genetic and phenotype variance, heritability and G x E interaction of rice mutant lines derived from gamma irradiation treatment on upland rice. This research was conducted in Situbondo and Madiun, during rain season. The analysis of variance (ANOVA) showed that DT15/11/KU and 1058/Cty mutant lines have higher yield compared with Situgintung (check variety). The grain yield per hectare from DT15/11/KU and 1058/Cty mutant lines were 7.76 ton ha-1and 7.18 ton ha-1respectively, with 12% of water content. Broad-sense heritability, genetic and phenotypic and environmental variances for agronomical traits such as filled grain per panicle, weight of 1,000 grain, yield per plot and yield per hectare were observed. The results showed that broad-sense heritability for weight of 1,000 grain was 94%, whereas other characters was less than 40%. Phenotypic variance was dominated by genetic variance for weight of 1,000 grain. Further selection for filled grain per panicle, yield per plot and yield per hectare needs to be conducted. G x E interaction and genotype were highly significant, whereas location variance was highly significant for filled grain and weight of 1,000 grains. Keywords: agronomic characters, broad-sense heritability, G x E interaction, genetic variance, upland rice